Apically extruded debris evaluation with the use of ProTaper Ultimate and TruNatomy files systems with and without glider preparation in primary tooth - Eskibaglar, Buesra Karaagac; Ozata, Merve Yeniceri (Mre Press, 2024)
Information regarding the influence of resorption and glide paths on debris extrusion in primary teeth is lacking. Therefore, we evaluated debris extrusion with and without resorption and with and without the use of a path file in primary molar teeth prepared with ProTaper Ultimate (PTU) Prime and TruNatomy (TRN) Prime rotary file systems. Forty resorbed and forty non-resorbed primary molar teeth were collected. Both groups were divided into four subgroups (n = 10). The Eppendorf tubes were weighed predebris. The distal canals of the teeth were prepared with PTU Prime and TRN Prime file systems, with and without the use of path files. The debris-filled tubes were weighed, and the weight of only the extruded debris was calculated by subtraction. The data were analyzed using a three-way analysis of variance (ANOVA) test. The presence of tooth resorption significantly increased debris extrusion, and the use of a path file significantly decreased debris extrusion (p < 0.001). The binary and ternary interactions of the three evaluated parameters among the groups showed no significant differences in terms of the amount of debris extruded (p > 0.05). While debris extrusion was observed in all groups, the use of a glide path file in primary teeth before the preparation process resulted in less debris extrusion.
Keywords: Apically extruded debris; Glide path; Nickel titanium file; Primary teeth; Root canal preparation